Silagem de cana-de-açúcar e de milho em dietas para bovinos de corte em confinamento - Roman, Juliano (2009)
The objective of this study was to evaluate the feasibility of using the sugar cane silage (SCS) in total mixed rations (TMR) for finishing beef cattle compared to use of corn silage (CS). The pattern of occurrence of dry matter (DML) and organic matter (OML) losses in CS and SCS stored in stack silo, and the effect of these silages on total mixed ration, with different formulation, on intake, performance, and carcass and meat characteristics were evaluated. The study of DML and OML was conducted to evaluate different parts inside the silo: three locations in the longitudinal direction (initial, medial and final) and two vertical (top and middle). The randomized blocks design in 3 x 2 factorial arrangement (three longitudinal locations and two vertical strata), with two replicates (silos) for CS and three replicates for SCS were used. The SCS was inoculated with Lactobacillus buchneri. It is estimated DML and OML through the use of tracer bags. The OML was also evaluated using the ash as an indicator (OMLi). In both silages, the DML, OML and OMLi were not affected (P>0.5) for longitudinal location in the silo, but vertically differed (P<0.03). In the CS, higher values were verified in the top layer (8.5, 9.2 and 18.7% respectively) compared with the middle layer (4.9, 5.2 and 7.3%, respectively). Inversely, the SDML, OML and OMLi in the SCS where higher (P<0.07) in the middle layer (22.2; 22.8 and 24.7 %) compared at the top layer (18.1%; 18.8% and 20.2%). In CS and SCS there was a positive correlation (r = 0.5 r = 0.3, respectively) between OML and OMLi, with adjustment to the linear regression model, but with low coefficients of determination (r² = 0.26 and r² = 0.11, respectively). The top layer of stack silo is critical in the spoilage of corn silage, but in sugar cane silage largest losses are found in the middle layer of the stack silo. Under proper unloading practices, losses remain constant during the use of the silo. The study of the use of SC and SM silage on animal performance and carcass characteristics involved the evaluation of five diets: CSF- diet containing corn silage, with formulation fixed during the period of feedlot; CSV: diet containing corn silage, with formulation variable according to the phase of feedlot; SCSF: diet containing sugar cane silage with formulation fixed; SCSV: diet containing sugar cane silage, with formulation variable; SCSV/CSV: CSV diet in initial half of feedlot and SCSV diet in final half. The completely randomized design, with five treatments and three replicates (collective pens) was used. Two hundred and thirty Nellore steers and 55 crossbreed, castrated, aged 36 months, initial body weight of 362.4 kg, were used. For the carcass evaluations were sampled 60 Nellore steers. The DM intake was higher (P<0.01) in diets containing corn silage (10.5 kg and 2.4% BW) than in diets containing sugar cane silage (10.1 kg and 2.3% BW). There was no effect (P>0.10) on average daily gain and body weight at slaughter: 1.348 kg and 481.2 kg, respectively. In SCSV/CSV diet, the feed conversion was worse (P = 0.08) than other diets (8.6 vs 8.0 kg DM/kg BW). The hot carcass weight (P = 0001), dressing percentage (P = 0001), subcutaneous fat thickness (P = 0.06) and fat tissue (P = 0.06) were higher in diets containing corn silage (262.1 kg, 54.1%, 6.2 mm and 34,6%, respectively) compared to the sugar cane silage (252.5 kg, 52.7%, 4.8 mm and 31,7% respectively). There was no effect (P>0,12) of the diets on the yield of primary meat cuts of the carcass. There was higher (P = 0,05) yield of strip loin and roast beef (% of hindquarter) in diets containing corn silage (10.0 and 6,9%) than diets containing sugar cane silage (9.0 and 6,6%). There was no effect of the diets evaluated on cooking losses (P>0.3) and shear force (P>0,14), with average of the 23.4% e 4.4 kgf/cm³, respectively. The performance, carcass and meat characteristics results demonstrate the feasibility of the use of sugar cane silage in diets for beef cattle. The adjustment of the formulation of the diet does not influence the performance, carcass and meat characteristics of finishing cattle. The replacement of sugar cane silage by corn silage during the feeding negatively affects feed conversion, but without influence on the carcass and meat characteristics of finishing beef cattle.